An Unsteady Pressure Probe for the Measurement of Flow Unsteadiness in Tidal Channels - Young, AM; Atkins, NR; Clark, CJ; Germain, G (IEEE, 2019)
IEEE An unsteady five-hole probe has been developed for the measurement of turbulent flow in tidal channels. Such measurements are vital for accurate prediction of unsteady loads on tidal turbines. Existing field-based velocimeters are either unable to capture the required range of frequencies or are too expensive to profile the variation of turbulence across a typical tidal power site, and thus the available data is inadequate for turbine design. This work adapts the traditional five-hole wind tunnel probe to achieve a low-cost device with sufficient frequency range for tidal turbine applications. The main issue in the marine environment is that the ambient hydrostatic pressure is much higher than the dynamic pressure. This has been overcome by using novel calibration coefficients and differential transducers. In flume tank tests against laser Doppler velocimeter measurements, the frequency response of the probe has been shown to be sufficient to capture all the frequencies necessary for tidal turbine design.
Keywords: 4012 Fluid Mechanics and Thermal Engineering; 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; 4015 Maritime Engineering